Teacher Development through Reflective Practice - Gnawali, Laxman (Journal of Education and Research, 2008)
How can teachers learn to understand themselves? Who and what can help them in this process? This paper attempts to establish that reflection is a key for teachers to explore not only their selves but also that of the others. When teachers carry out systematic enquiry into themselves, they will understand themselves, their practices and their learners. By constantly looking into their own actions and experiences, they can professionally grow in their own work places. ! is paper discusses the process of reflection and how it actually works for teacher professional development. DOI: http://dx.doi.org/10.3126/jer.v1i0.7953 Journal of Education and Research 2008, Vol. 1, No. 1, pp. 69-71